On the derivation of reaction-diffusion equations as limit dynamics of systems of moderately interacting stochastic processes - Oelschläger, Karl (Probability theory and related fields, 1989)
We consider systems of "moderately" interacting particles, which are divided into a finite number of different subpopulations, and show that in the limit as the population size tends to infinity the empirical processes of the subpopulations converge to the solution of a system of reaction-diffusion equations.